Effectiveness Of Problem Solving And Decision Making Skill On Professionals Performance In IT Industry (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper is centered on the unique context of soft skill training for IT  professionals. While existing literature often concentrate on training methods in various sectors, only a limited number of studies have delved into the IT sector. Additionally, this article places significance on the timing and duration of  training and its effectiveness on professional performance. This study highlights that improved performance among professionals in specific companies can be attributed to their acquisition of soft skills through training. Furthermore, this paper offers clarity regarding the effectiveness of soft skill training, with a particular focus on problem solving and decision making skills. These skills are seen as crucial for enhancing employee performance, which in turn is vital for an organization’s sustainability.